Investigation of the method of chemical desorption for extraction of nikel ions (II) from bentonite clays - Sakalova, Galyna; Vasylinycz, Tamara; Koval, Nataliya; Kashchei, Viktoriia (Lviv Politechnic Publishing House, 2017)
The problem of accumulation of spent sorbents is considered in the article; The main methods of desorption of pollutants and regeneration of sorbents are described; the effectiveness of the method of chemical desorption for extracting Nikel ions (II) from bentonite clays is investigated; the main ways of utilization of spent sorbents are considered.
Keywords: bentonite clay; utilization; regeneration; chemical desorption